International Students in First-Year Writing: A Journey Through Socio-Academic Space - Schmidt, Anthony (Journal of International Students, 2019)
International Students in First-Year Writing: A Journey Through Socio-Academic Space describes the lived experiences of ten international students enrolled in a first-year writing (FYW) course at an American university.